Study of newly diagnosed Gastroenterology tumors and associated risk factors at Tishreen University Hospital in Lattakia – Syria - Alyahia, Akel Khaled; Zaizafoun, Hassan; Dugman, Daed (Journal of medical and pharmaceutical sciences, 2021)
Objective: The study was conducted in order to determine the epidemiological characteristics of referred patients at Tishreen University Hospital in Lattakia and who have been diagnosed with one of the types of malignant Gastrointestinal tumors and study the distribution of risk factors in these patients. Patients and Methods: An Observational Descriptive study (Cross- Sectional) conducted for the period from January 2020 to January 2021 at Tishreen University Hospital in Lattakia- Syria (in Gastrointerolog Department). The variables analyzed were age, gender, tumor location and risk factors Results: The research sample included 223 patients (127 males and 96 females). Esophageal tumors are relatively rare and most of them are of the squamous cell carcinoma type (72.8%). Stomach tumors are the second most common tumor with a percentage of (23.8%), and adenocarcinoma constituted 89% of the cases. Colon and rectal cancer represented the largest percentage (35%) of gastrointestinal tumors, and half of these tumors were in the rectum. Pancreatic cancer ranked third with 11.2% of cases. Tumors of the small intestine and gallbladder and hepatocellular carcinoma are relatively rare. Our most frequently seen risk factors were smoking in most tumors, positivity for H. pylori in 70% of gastric adenocarcinoma patients, and family history and inflammatory bowel disease in Colon tumor patients. Conclusion: Although the incidence of some gastrointestinal cancers has decreased, these cancers continue to pose major challenges to public health, especially colorectal tumors.